A History of Victims of Crime: How They Reclaimed Their Rights - Strauss-Walsh, Stephen J. (Routledge Contemporary Issues in Criminal Justice and Procedure Series, 2023)
Cover -- Endorsement Page -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Acknowledgements -- Table of Instruments -- Case Law -- Chapter 1 Introduction -- Context -- Research question -- Methodology -- Contribution to knowledge -- Structure -- Part I Historical context -- Chapter 2 A contextual study of victim centrality in eighteenth-century Britain -- Introduction -- The eighteenth century -- Politics -- The victim of crime -- In the popular imagination -- Compounding -- Conclusion -- Chapter 3 The causes and outcomes of the exclusion of victims from the nineteenth century Irish justice system -- Introduction -- The nineteenth-century causes of victim exclusion -- A fading noblesse oblige and a laissez-faire revolution -- Urbanisation within an industrialising Ireland -- Greater resident numbers move to cities -- Problems with the victim-centred system are emphasised -- The prevalent hesitancy regarding pursuing actions -- Britain's closest colony lists towards revolution -- British hegemonic rule becomes almost impossible -- The "fear of the crowd" and a move from "status to contract" -- Disorder sees social unrest become a persistent Irish issue -- The"Leviathan State" engenders punitive advancements -- Novel organisations begin dictating chastisement -- Reform alters regulation of juridical frames -- Traditionally overlooked transgressions Are prosecuted -- The impact of victim exclusion in nineteenth-century Britain -- Punishment becomes successfully centralised -- Conclusion -- Part II Sociological transformation -- Chapter 4 Feminism and victimology highlight hidden victimisation -- Introduction -- Victimology -- The birth of the study of victims -- Feminism -- Consciousness-raising and -changing -- Conclusion -- Chapter 5 Domestic drivers of change re-establish the victim.